FENOMENA JILBOOBS DALAM PANDANGAN ISLAM - Nurlaili Dina Hafni (Al Hikmah: Jurnal Studi Keislaman, 2016)
In this era, “Jilbab” has been a distinct trend for fashion Muslim woman with an increasingly diverse and interesting. Can already see in various public places, the hijab is now increasing and varied preserving the Muslim clothing that covers the body. In everyday life the word fashion is more often defined as makeup or style and fashion, there are also those who define fashion as clothing or wearing apparel. Fashion has also become a symbol of class and social status of the wearer, it is also a socio-cultural representation that is close to our daily life. On the other hand technological developments that grow fast and innovative, recently appeared several new social media more specific uses, such as for example is instagram. Due to the emergence instagram then the impact on the increasing number of photo hobbyists who suddenly explode. Increasing number of connoisseurs and craze photos then used by some people to create an account on a person's profile, community, lifestyle, and much more. one of them is dressed Jilboobs lifestyle.